Research and application on key techniques of marine IoT - Fengzhong QU; Hangliang LAI; Jianzhang LIU; Xingbin TU; Yuan JIANG (Dianxin kexue)
Ocean observation networks with isolated and fragmented sensor data are not able to meet the demands of current ocean monitoring.Marine internet of things (IoT), which has the advantage of low investment cost, low power consumption, and interconnection is the primary research direction in the area of ocean information.An overview of the development and status of ocean observation networks was presented.A new type of marine IoT system architecture was proposed based on the Zhejiang University - Zhairuoshan Experimental Research Observatory (Z2ERO).It features key marine IoT devices and test platforms, including scientific instrument interface module, hydroacoustic communicators, narrow-band IoT floating balls, seafloor test platforms, and portable acoustic retrievers.Future marine IoT is expected to develop toward miniaturization, intelligence, and diversity of communication methods.With the support of the terrestrial internet, the internet of everything will be achieved through an integrated space-air-ground-sea network.